The effect of science instruction integrated with unplugged computational thinking activities on students’ academic achievement and computational thinking skills - Kılıç, İlayda (My University, 2021)
Computational thinking (CT) is a significant competency of 21st-century skills. The acquisition of computational thinking skills has become an important debate in science, technology, engineering and mathematics disciplines. This study enlightens the potentiality of computational thinking integrated instruction in K-12 science classrooms. The purpose of this study is to find out the impact of unplugged CT activities during the subject of pure matter and mixtures on seventh-grade students’ academic achievement and CT skills. The study has a quasi-experimental design with a non-randomized control group to which a pre-test and a post-test were administered in two regular science classrooms in a public middle school located in Uskudar/Istanbul. The experimental group was subjected to a treatment of unplugged CT based constructivist science instruction, while the students in the control group were treated based on the constructivist approach. Consequently, there were statistically significant differences between before and after treatment in the experimental group regarding the achievement in the subject of pure matter and mixtures and CT skills, with a large size effect (d= 1.56) on achievement in the subject of pure matter and mixtures, and a large size effect on CT skills (d= 0.95). CT skills of the control group did not show a statistical distinction between pre-test and post-test, and academic achievement in the control group elicited a statistically significant difference between pretest and post-test indicating a large size effect (d= 1.49) in favour of the post-test. It was also found out that there was a meaningful difference between the post-test scores of CT skills of the experimental and the control group. However, there was no significant difference in the post-test scores of subject-specific success between the experimental group and the control group. Finally, interpretation and discussion were provided in line with research findings.

Bilgi işlemsel düşünme 21. yüzyılın önemli becerileri arasında yer alır. Bilgi işlemsel düşünme becerisinin itibaren kazanımı fen, teknoloji, mühendislik ve matematik disiplinlerinde önemli bir tartışma konusu olmuştur. Bu araştırma, bilgi işlemsel düşünme ile bütünleştirilmiş öğretimin K-12 düzeyindeki fen bilimleri derslerine sunduğu imkanlara ışık tutmaktadır. Bu çalışmanın amacı dijital araç kullanımını içermeyen bilgi işlemsel düşünme etkinliklerinin yedinci sınıf öğrencilerinin saf madde ve karışımlar konusundaki akademik başarılarına ve bilgi işlemsel düşünme becerilerine olan etkisini incelemektir. Ön-test ve son-test kontrol gruplu yarı deneysel desen İstanbul ili Üsküdar ilçesindeki bir devlet ortaokulundaki iki sınıfta uygulanmıştır. Deney grubunda dijital araç kullanımını gerektirmeyen bilgi işlemsel düşünmeyle bütünleştirilmiş yapılandırmacı fen öğretimi uygulanırken; kontrol grubunda yapılandırmacı yaklaşım kullanılmıştır. Sonuç olarak, deney grubunda uygulama öncesi ve sonrası arasında saf madde ve karışımlar konusundaki başarıda ve bilgi işlemsel düşünme becerisinde istatistiksel olarak anlamlı fark bulunmuştur. Bu farkın akademik başarıya büyük bir etkisi olduğu (d= 1.56) ve bilgi işlemsel düşünme becerilerine büyük bir etkisi olduğu (d= 0.95) bulunmuştur. Kontrol grubu bilgi işlemsel düşünme becerileri ön-test ve son-test puanları istatistiksel olarak anlamlı bir farklılık göstermemiştir. Kontrol grubunun akademik başarısında ön-test ve son-test puanları arasında son-test lehine istatistiksel olarak anlamlı bir fark çıkmıştır ve bu farkın büyük bir etkiye sahip olduğu bulunmuştur (d= 1.49). Ayrıca deney ve kontrol grubunun bilgi işlemsel düşünme becerilerine ilişkin son test puanları arasında anlamlı bir farklılık olduğu bulunmuştur. Fakat uygulama sonucunda gruplar arasında saf madde ve karışımlar konusundaki başarıda istatistiksel olarak anlamlı bir fark yoktur. Son olarak ise araştırma sonuçlarına uygun olarak yorum ve tartışma yapılmıştır.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2021
Keywords: Bilgi işlemsel düşünme; Fen eğitimi; Akademik başarı; Computational thinking; Science education; Academic achievement